‘Abstract Machine’. Diagrams in Project Narrative (diségno, 2023)
In the successful relationship between architecture and communication, between project and narrative, between construction and image, the diagram certainly occupies an important position.In the contemporary design practice’s shift towards prefiguring broad, open, deferrable, indeterminate and perfectible scenarios, the diagram’s effectiveness seems to lie precisely in its ability to transfer complex systems, phenomena and concepts in an immediate and complete way. This mainly graphic form of schematisation seems to configure itself as the most suitable tool for gathering the tensions of a time that is beginning to distance itself from formal perfection and authorial needs in order to slide from the architectural object to the design process.The diagram is thus simplified, through a schematic didactic organisation: if it can prefigure the form of an architecture, describe its function and/or uses, the relationship between its parts, highlight a theme, an idea, a concept, here we are interested in highlighting its usefulness in the narrative construction of the design process, even ex post. The contribution therefore intends to propose a didactic ‘deconstruction’ of the diagram, with an inevitable simplification and reduction of its rich complexity, justified by the desire to propose not so much a definition of what the diagram is, but rather how it can be used.
Keywords: diagram; process; narrative